2020
DOI: 10.33003/fjs-2020-0403-251
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Serum Biochemical Profile in Yankasa Rams Fed Alkali-Treated Groundnut Shells

Abstract: The study was conducted to assess the chemical composition of alkali treated groundnut shells and their effects on growth and serum biochemical parameters in Yankasa rams. A total of 4 Yankasa rams where used to conduct the experiment in a 4×4 Latin square design. Four diets (14% crude protein) were formulated to contain untreated groundnut shell (UTGNS), urea treated groundnut shell (UGNS), lime treated groundnut shell (LGNS) and urea-lime treated groundnut shell (ULGNS). Growth and blood serum parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…It may also be as a result of a better nutrient absorption and utilization by the rams diet T5 (20%) which resulted in a higher total weight gain and daily weight gain as compared to those fed diet T2 (5%), T3 (10%) and T4 (15%%) (McDonald et al, 2011). The decreased feed intake and low weight gain observed in animals on T2, T3 and T4 in this study was similar to the findings of Millam (2020) when they fed Urea treated groundnut shell along with maize offal in a complete diet to Yankasa rams. The high feed intake in the animals receiving 20% UTGNSM diets (T5) in this study was in consonance with the findings of Abdel Hameed et al (2013) and Kade (2020) who reported that lambs fed treated GNS had increased feed intake.…”
Section: Discussionsupporting
confidence: 87%
“…It may also be as a result of a better nutrient absorption and utilization by the rams diet T5 (20%) which resulted in a higher total weight gain and daily weight gain as compared to those fed diet T2 (5%), T3 (10%) and T4 (15%%) (McDonald et al, 2011). The decreased feed intake and low weight gain observed in animals on T2, T3 and T4 in this study was similar to the findings of Millam (2020) when they fed Urea treated groundnut shell along with maize offal in a complete diet to Yankasa rams. The high feed intake in the animals receiving 20% UTGNSM diets (T5) in this study was in consonance with the findings of Abdel Hameed et al (2013) and Kade (2020) who reported that lambs fed treated GNS had increased feed intake.…”
Section: Discussionsupporting
confidence: 87%
“…This may have an impact on production performance because of the low nutritional value of the roughage feeds, particularly wheat straw, which is the primary roughage feed material used in animal nutrition due to its high fiber and low protein content [1]. Numerous prior investigations have examined the application of alkali pre-treatments, including calcium hydroxide, ammonization, sodium hydroxide, and urea, to enhance the digestibility of roughages and improve the growth performance of small ruminants [2][3][4]. Exogenous enzymes, particularly fibrolytics, show promise for enhancing feed utilization and improving ruminant productivity [5].…”
Section: Introductionmentioning
confidence: 99%
“…chemical composition was according to the international methods of AOAC[12] 2 concentrate diet contained: 45% barley grain, 7% yellow corn, 35% wheat bran, 10% soybean meal, 1% limestone, 1% salt and 1%Premix 3. calculated NFE = OM-(CP+CF+EE)4 calculated ME (MJ/ kg DM) = 0.012CP +0.031EE+0.005CF +0.014NFE[13] …”
mentioning
confidence: 99%